The Impact of Remittance toward Indonesia’s Economic Growth - Nur Siti Annazah; Ivan Suryono (Nusantara Science and Technology Proceedings, 2020)
This paper aims to find out external factor toward long-term economic growth. Variable used are remittance, PMTB, import and economic growth obtained from World Development Indicator (WDI) in period of 1988-2018. Regression analysis of ARDL Cointegration is utilized in finding out remittance, PMTB and import toward economic growth both for short-term and long-term. The result of analysis shows that remittance affects toward long-term economic growth. PMTB variable can increase economic growth both for short-term and long-term. Import variable can increase economic growth in short-term, but it decreases economic growth in long-term. The result shows that external factors need to be paid attention more by government because it can contribute toward national economic growth